The involvement of the sigma-1 receptor in neurodegeneration and neurorestoration - Karsten Ruscher; Tadeusz Wieloch (Elsevier, 2015)
The sigma-1 receptor (Sig-1R) is a single 25 kD polypeptide and a chaperone protein immersed in lipid rafts of the endoplasmic reticulum (ER) where it interacts with mitochondria at the mitochondria-associated ER membrane domain (MAM). Upon activation, the Sig-1R binds to the inositol trisphosphate receptor (IP3R), and modulates cellular calcium (Ca2+) homeostasis. Also, the activated Sig-1R modulates plasma membrane receptor and ion channel functions, and may regulate cellular excitability. Further, the Sig-1R promotes trafficking of lipids and proteins essential for neurotransmission, cell growth and motility. Activation of the Sig-1R provides neuroprotection and is neurorestorative in cellular and animal models of neurodegenerative diseases and brain ischaemia. Neuroprotection appears to be due to inhibition of cellular Ca2+ toxicity and/or inflammation, and neurorestoration may include balancing abberant neurotransmission or stimulation of synaptogenesis, thus remodelling brain connectivity. Single nucleotide polymorphisms and mutations of the SIGMAR1 gene worsen outcome in Alzheimer's disease and myotrophic lateral sclerosis supporting a role of Sig-1R in neurodegenerative disease. The combined neuroprotective and neurorestorative actions of the Sig-1R, provide a broad therapeutic time window of Sig-1R agonists. The Sig-1R is therefore a strong therapeutic target for the development of new treatments for neurodegenerative diseases and stroke.